2014
DOI: 10.1124/jpet.114.215921
|View full text |Cite
|
Sign up to set email alerts
|

Complement Inhibition in Cynomolgus Monkeys by Anti–Factor D Antigen-Binding Fragment for the Treatment of an Advanced Form of Dry Age-Related Macular Degeneration

Abstract: Anti-factor D (AFD; FCFD4514S, lampalizumab) is a humanized IgG Fab fragment directed against factor D (fD), a rate-limiting serine protease in the alternative complement pathway (AP). Evaluation of AFD as a potential intravitreal (IVT) therapeutic for dry age-related macular degeneration patients with geographic atrophy (GA) is ongoing. However, it is unclear whether IVT administration of AFD can affect systemic AP activation and potentially compromise host-immune responses. We characterized the pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 43 publications
5
50
0
3
Order By: Relevance
“…However, literature on ITV administration of anti-vascular endothelial growth factor therapy suggested that the half-life of ranibizumab (7-9 days) (Krohne et al, 2012;Xu et al, 2013) was only slightly shorter than that for bevacizumab (9.8 days) (Krohne et al, 2012) in humans. Notably, the quasi-steady state equilibrium constant K ss was fixed to the in vitro measured value of the dissociation equilibrium constant (K D ) of 11.7 pM (Loyet et al, 2014) and was able to describe the data quite well. As the quasi-equilibrium approximation is a special case of the quasi-steady state approximation (Gibiansky et al, 2008), and the in vitro and in vivo agreement of the parameters K D and K ss confirms the assumption that the internalization rate constant is much smaller than the dissociation rate constant.…”
Section: Tmdd Model Of Lampalizumab In Cynomolgus Monkeysmentioning
confidence: 99%
See 4 more Smart Citations
“…However, literature on ITV administration of anti-vascular endothelial growth factor therapy suggested that the half-life of ranibizumab (7-9 days) (Krohne et al, 2012;Xu et al, 2013) was only slightly shorter than that for bevacizumab (9.8 days) (Krohne et al, 2012) in humans. Notably, the quasi-steady state equilibrium constant K ss was fixed to the in vitro measured value of the dissociation equilibrium constant (K D ) of 11.7 pM (Loyet et al, 2014) and was able to describe the data quite well. As the quasi-equilibrium approximation is a special case of the quasi-steady state approximation (Gibiansky et al, 2008), and the in vitro and in vivo agreement of the parameters K D and K ss confirms the assumption that the internalization rate constant is much smaller than the dissociation rate constant.…”
Section: Tmdd Model Of Lampalizumab In Cynomolgus Monkeysmentioning
confidence: 99%
“…A target-mediated drug disposition (TMDD) model is critical in explaining the PK and PD of many biologics for which the high antibody-target binding affinity as well as the antibody and target levels can directly influence the PK of the antibody (Mager and Jusko, 2001). Lampalizumab was shown to bind CFD in both human and cynomolgus monkey (Macaca fascicularis) species with high affinity (Loyet et al, 2014). Cynomolgus monkeys were shown to be a relevant preclinical model for evaluating the PK/PD of lampalizumab Loyet et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations